Perancangan Table Set Multifungsi Untuk Ruang Hunian Terbatas - Alexander Ferdinand Sudarji; Adi Santosa; Grace Setiati Kattu (Intra, 2019)
In this design, the designer wants to find alternative designs in making table sets with different constructions. One alternative construction is folding construction because the rapid growth of population makes land for housing become narrow and expensive, therefore middle to lower society prefer small home such as apartment. Seeing the situation, the designer wants to design a furniture that uses folding construction to cope with places with limited occupancy space, the designer began to search for information related with folding furniture, such as advantages, disadvantages, how to process and so on. With the information, the designer began to make design concepts, and the concept resulted in a multifunctional table set design with folding construction that could answer the existing design problems.